DASAR DAN PROSEDUR (KAJIAN TERHADAP KITAB UNDANG-UNDANG HUKUM ACARA PIDANA) - Umi Enggarsasi (Perspektif, 2004)
Pre-Judicature Institution as a supervision means against investigators and general prosecutors that have carried out attempts by force to defendants in terms of accomplishing their duties namely actions of captures, arrests, examination-termination and prosecution-termination. Societal law-awareness affects lawsuits of prejudicature submitted to the court to have fair and just treatments in examination processes ranging from processes of examination, investigation to prosecution. By means of normatively juridical review, thus we can find out legal foundations of prejudicature in Indonesia, backgrounds of plaintiffs in pre-judicature lawsuits and procedures of pre-judicature lawsuits take form of claims of compensation and rehabilitation due to mistakes of law enforcing officials.